Representing groups of students as personas: A systematic review of persona creation, application, and trends in the educational domain - Ali Farooq; Amani Alabed; Pilira Stella Msefula; Reham AL Tamime; Joni Salminen; Soon-gyo Jung; Bernard J. Jansen (Computers and Education Open)
This study presents a comprehensive systematic review of the use of student personas in education, drawing insights from 83 publications identified through the ACM Digital Library, Web of Science, and Scopus. The analysis reveals that qualitative methodologies dominate persona development, with limited adoption of data-driven algorithmic approaches. Most studies constructed small persona sets—typically four or fewer—focusing on dimensions such as behaviors, beliefs, goals, needs, experiences, perceptions, and demographics, contrasting with larger sets found in industry. Predominantly featured in educational conferences, student personas were employed to (1) understand user needs, goals, and behaviors, (2) support the design and development of learning systems, (3) enhance teaching and learning practices, (4) facilitate persona-based roleplaying, and (5) promote diversity, inclusivity, and accessibility. However, the assessment of personas’ impact in these areas remains minimal. The findings suggest significant opportunities for the educational sector to leverage algorithmic methods to advance persona creation and broaden their application scope.